Effect of Temperature on Mechanical Properties of Pure Copper - Mohd Murad, Nur Aida Muzirah; Dr. MOHD YUSSNI BIN HASHIM (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Copper is an essential element for major industrial metal because of its high ductility, malleability, thermal and electrical conductivity and resistance to corrosion. Copper and its alloy are mainly used in wiring production, piping, automotive and architecture. Unfortunately, some copper and copper alloys need to undergo heat treatment process in order to attain the desired properties for each applications. Based on the characteristics of material, the changes in mechanical and physical properties takes place at different critical temperatures. As a result, the exposure of copper to different temperature in this research (100°C, 200°C and 300°C) with time of 1 hour, 2 hours and 3 hours is to study the change in tensile properties referring to tensile strength, and elongation, as well as its hardness. This study explores the basic connection between changes in temperature and the mechanical properties of pure copper. The mechanical characteristics—such as hardness, ductility, and tensile strength—were methodically investigated at various temperatures. Using cutting-edge technology, pure copper specimens were tested under controlled circumstances with different temperatures to mimic real-world temperature scenarios.